2011
DOI: 10.5551/jat.7526
|View full text |Cite
|
Sign up to set email alerts
|

Flow-Mediated Dilation is Associated with Microalbuminuria Independent of Cardiovascular Risk Factors in Type 2 Diabetes

Abstract: Aims:To investigate whether endothelial dysfunction assessed by brachial artery flow-mediated dilation (FMD) is associated with urinary albumin excretion (UAE) and is interrelated with carotid intima-media thickness (IMT) and pulse-wave velocity (PWV) in type 2 diabetes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
21
1
2

Year Published

2012
2012
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 32 publications
1
21
1
2
Order By: Relevance
“…In accordance with our findings previously reported data have not shown an association of glycemic control with endothelial dysfunction [31,33]. On the other hand, endothelial dysfunction has been previously related to the presence and levels of cardiovascular risk factors in T2DM patients [23,29,30], although not consistently [34], while vascular inflammation has been suggested to play a central role in the development of endothelial dysfunction [35]. It should be noted that compared to other reports [23,29,30], our study included T2DM patients with severely impaired FMD (mean FMD 1.98%) and a high prevalence of accumulated cardiovascular risk factors; in these patients longer duration of diabetes, and not other established cardiovascular risk factors, was the only important determinant of endothelial dysfunction.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In accordance with our findings previously reported data have not shown an association of glycemic control with endothelial dysfunction [31,33]. On the other hand, endothelial dysfunction has been previously related to the presence and levels of cardiovascular risk factors in T2DM patients [23,29,30], although not consistently [34], while vascular inflammation has been suggested to play a central role in the development of endothelial dysfunction [35]. It should be noted that compared to other reports [23,29,30], our study included T2DM patients with severely impaired FMD (mean FMD 1.98%) and a high prevalence of accumulated cardiovascular risk factors; in these patients longer duration of diabetes, and not other established cardiovascular risk factors, was the only important determinant of endothelial dysfunction.…”
Section: Discussionsupporting
confidence: 92%
“…In T2DM patients without macrovascular or microvascular disease, we found that endothelial dysfunction, as assessed by reduced brachial artery FMD, was independently associated only with the duration of diabetes; for every 10 years of diabetes, FMD is reduced by approximately 1.0% (in absolute FMD values). Previous studies have shown significant associations of FMD with diabetes duration [29,30] although not consistently [31]. Longer T2DM duration has also been shown to increase CVD risk and total mortality significantly even after adjustment for established and novel cardiovascular risk factors [32] suggesting that there might be a link between T2DM duration, worsening endothelial function and cardiovascular prognosis in these patients.…”
Section: Discussionmentioning
confidence: 95%
“…Although the relationships between MAU and endothelial dysfunction, as well as with impaired endothelial function in hypertensive patients with CP, have been investigated in several studies, 3,4) the superposition of two OD parameters such as MAU and CP in association with endothelial function remains unclear.…”
mentioning
confidence: 99%
“…25) Benidipine has been reported to improve vascular endothelial function in basic and clinical research. 10,26) Our study suggested that benidipine might be superior to amlodipine in improving AI and UAE, which may be accounted for by the vascular protective effects of benidipine, including improvement in vascular endothelial function.…”
Section: Discussionmentioning
confidence: 99%